The Strategic Contribution of Diversity, Equity, and Inclusion in Advancing Employee Engagement toward Workplace Sustainability in Indonesia’s Herbal Medicine Industry - Latief, Lutfillahi; Prayitno, Agus; Ingsih, Kusni; Purwaningsih, Aris Puji (JURNAL MANAJEMEN MOTIVASI, 2025)
The imperative to cultivate an inclusive, equitable, and diverse work environment has become increasingly prominent in contemporary organizational discourse, especially when it comes to keeping employees engaged and supporting the long-term health of an organization. In Indonesia’s herbal medicine industry, a sector marked by strict regulations and a diverse employee base these inclusive values are often discussed but not always fully explored in practice. This paper investigates how the adoption of these values fosters employee loyalty and how such loyalty functions within the framework of organizational sustainability, in turn, helps the company stay sustainable over time. Employing a quantitative research paradigm, this study elicited empirical data from 367 employees embedded within Indonesian enterprises affiliated with the United Nations Global Compact (UNGC). This study utilized PLS-SEM as the primary analytical method to explore the relationships between inclusivity, employee involvement, and outcomes related to sustainability. The results showed a strong link, inclusive policies boosted both employee commitment and the company’s overall sustainability goals. Moreover, employee engagement was recognized as a connecting mechanism linking inclusive strategies with sustained organizational outcomes. Ultimately, this research underscores that when organizations foster an environment built on fairness and openness, employees tend to be more motivated, collaborative, and creative qualities that are essential for innovation and resilience. The study also provides clear, actionable steps for companies aiming to tie their HR strategies more closely to sustainability, particularly in industries where compliance and ethical standards are a top concern.